The relationship between screen time and social skills of children aged 2–4 years in the family environment - Eka Fitrianih; Nurjanna Nurjanna; Wilda Resky Pratiwi; Hamdiyah Hamdiyah; Asmah Sukarta; Siti Hasriani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: The development of social skills in children aged 2–4 years is a crucial foundation for shaping personality and future interpersonal relationships. However, technological advancements have led to an increase in children’s screen time duration, which is feared to potentially hinder their social development. Purpose: to examine the relationship between screen time duration and social skills among children aged 2–4 years within the family environment. Method: This research employed a quantitative approach with a descriptive correlational design. The population consisted of all children aged 2–4 years in Kembangragi Village, Selayar Islands Regency, totaling 80 children, with the entire population included as the sample (total sampling). Data were collected using structured questionnaires and observation and then analyzed using correlation tests. Results: The analysis revealed that most children had more than 2 hours of screen time per day. Lower levels of social skills were more frequently observed among children with higher screen time. A significant relationship was found between screen time duration and children’s social skills (p < 0.05), indicating that the longer the screen time, the lower the social skills. Conclusion: There is a significant relationship between screen time and social skills in children aged 2–4 years. Therefore, parental supervision and regulation of screen time are necessary to support children’s optimal social development. Suggestion: Future researchers are advised to use a mixed methods approach to obtain a more comprehensive picture of the quality of screen time interactions and its impact on child development.